Functional Use of Directional Local Field Potentials in Parkinson's Disease. (1st September 2019) - Telkes, Ilknur; Durphy, Jennifer; Adam, Octavian; Raviv, Nataly; Pilitsis, Julie G
Abstract: INTRODUCTION: One of the biggest limitations of deep brain stimulation (DBS) therapy is the stimulation induced side effects due to restricted size of functional areas in subthalamic nucleus (STN) and the proximity of structures. The segmented DBS lead technology aims to address this problem by delivering more selected, focal modulation via smaller, directional contacts. However, the DBS programming becomes more complex and time-consuming for clinical feasibility. Here in this pilot study, we investigated the spectral power distribution of directional local field potentials (LFPs) in STN and their relationship to motor symptoms of Parkinson disease (PD). METHODS: We recorded 8-channel intraoperative LFPs in 9 PD patients at resting and during stimulation OFF. Power-frequency spectra were computed for all individual contacts and then grouped according to which anatomical directions they are facing. Beta (13-20 Hz/20-35 Hz) and alpha (7-12 Hz) band powers were calculated and their correlation to preoperative UPDRS-3 scores (51.7 ± 21.9 d before the DBS surgery) and the clinical programming were evaluated. RESULTS: The average depth-frequency maps demonstrated different spectral dynamics across anterior, medial, and lateral directions. Patients with severe tremor compared to nontremor subjects showed higher beta power in anterior and lateral directions. Beta band power were positively correlated with the tremor severity and significantly correlated with clinical stimulation amplitude (mA) in anterior direction ( P  < .05). Correlation analysis between beta power and the other UPDRS-3 items such as bradykinesia/rigidity or postural instability and gait disturbance did not show clear trends towards a direction. CONCLUSION: Given that testing all possible combinations of contact pairs and stimulation parameters is not feasible in a single clinic visit, spatio-spectral dynamics obtained from intraoperative recordings of LFPs might be used as an initial marker to select optimal contact (s). LFPs carry pathological signatures of PD and they might provide a functional use to predict optimal stimulation parameters in future. These features as well as higher frequency and cross-coupling dynamics of LFPs need to be studied in detail with larger subject populations.